A violência contra as mulheres e o feminicídio - Kitamura, Camila Marques Leoni (2021)
Violence against women can be understood as a worldwide phenomenon. This situation can be verified in all races, social classes, ages, religions, at any time and place. humanity. Violence can occur in several ways: physical, psychological, sexual, virtual, economic, or financial and property, in some cases it reaches murder or as it came to be called femicide. Law n. 11.340/2006 (Law Maria da Penha) and Law n.13.104/15 (Feminicide Law) emerged in order to inhibit domestic and family violence. In this context, this dissertation aims to investigate the violence suffered by women and the effects on their lives; what are the perceptions, the consequences, and the reasons for staying in that situation. The method used was research-intervention derived from institutional analysis. In the research process, women who attend two support centers, the OGN’s Bem Querer Mulher and Casa Eliane Grammont, were interviewed, as well as a family, especially a mother. The researcher these women were described, who reported their suffering, seeking to highlight the singularities of each person’s experiences. The word “women” was used extensively during the research. The women portrayed in the survey are cis and straight but are not mentioned as a universal model. Public policies in this field, desoite the efforts of the professionals who compose them, are weakened, and linked to government policies, which do not always consider them a priority. The research emphasizes the importance of undertaking services in reception / care from an intersectional perspective, in addition to strengthening collective spaces for works and users